2006
DOI: 10.1212/01.wnl.0000201185.91110.15
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the paraplegin gene ( SPG7 ) in patients with hereditary spastic paraplegia

Abstract: SPG7 mutations account for less than 5% of hereditary spastic paraplegia (HSP) families compatible with autosomal recessive inheritance. Cerebellar signs or cerebellar atrophy on brain imaging were the most frequent additional features in patients with SPG7 HSP. Rare nucleotide variants in SPG7 are frequent, complicating routine diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 18 publications
10
107
1
3
Order By: Relevance
“…This was the case for SPG7 (paraplegin) and SPG5 (CYB7B1). 16,17,22,23 In terms of disease progression, SPG30 differs from other ARHSPs, such as SPG11, 24 in having a less severe evolution, as all affected members were still able to walk after disease durations of between 9 and 22 years even if maximal walking distance was reduced in all patients.…”
Section: Spg30 Phenotypementioning
confidence: 95%
“…This was the case for SPG7 (paraplegin) and SPG5 (CYB7B1). 16,17,22,23 In terms of disease progression, SPG30 differs from other ARHSPs, such as SPG11, 24 in having a less severe evolution, as all affected members were still able to walk after disease durations of between 9 and 22 years even if maximal walking distance was reduced in all patients.…”
Section: Spg30 Phenotypementioning
confidence: 95%
“…4 Since then, a significant number of causative mutations were found in several HSP cohorts from different populations. [5][6][7][8][9][10][11][12][13][14] SPG7 can be characterized by a pure or complex HSP phenotype. Increasingly, reports documented that cerebellar ataxia and cerebellar atrophy on magnetic resonance imaging (MRI) are the most frequent additional features in complex SPG7 cases.…”
Section: Introductionmentioning
confidence: 99%
“…The p.His448Profs * 12 mutation is predicted to result in a premature stop codon. Previous reports (7,(9)(10)(11)(12)(13)(14)(15) have revealed that missense and nonsense mutations located closer to the C-terminal of paraplegin than the p.His448Profs * 12 mutation can cause disease ( Figure D). Recently, genotype-phenotype correlations were identified for SPG7: an association between cerebellar ataxia and SPG7 null alleles leading to an absence of protein products or severely truncated protein products and an association between optic nerve atrophy and a missense mutation in exon 10 (pArg470Gln) (9).…”
Section: Discussionmentioning
confidence: 85%